Water supply and sanitation status in educational institutions at Mirzapur of Tangail district, Bangladesh - Mahmuda Binte Latif; Tanmoy Roy Tusher; Jewel Khan; Muhammad Solaiman Mia; Muliadi Muliadi; Shamim Al Mamun (Hasanuddin University, 2017)
The study was conducted to assess the quality of drinking water supply and sanitation status in educational institutions at Mirzapurpourashava of Tangail district during the period of January to February 2014. The water samples were collected from tube wells of 15 different educational institutions, while a questionnaire survey of 150 respondents based on reconnaissance survey was performed in order to investigate the drinking water quality and sanitation status of 15 selected educational institutions. The study found the pH ranged from 7.23 to 7.95, EC from 264 to 542 µS/cm, TDS from 136 to 272 mg/l, DO from 1.90 to 4.30 mg/l, hardness from 120 to 298 mg/l, and Fe from0 to 10 mg/l. All the observed water quality parameters were relatively within the standard limits for Bangladesh except DO, whereas Fe concentrations in three primary schools also exceeded the standard value of Bangladesh drinking water quality of 0.3-1.0 mg/l. The survey results revealed that mainly two types of tube wells i.e. shallow tube wells and Tara pump tube wells were used for water supply in those educational institutions, while maximum tube wells were with a depth of 140-180 feet (47% of tube wells), 100-140 feet (23% of tube wells) and from 180-220 feet (rest 30%). No soap and/or toilet tissue was found in 40% toilets, while 60% toilets were with soap and/or toilet tissue facilities. The study observed that the existing water supply and sanitation facilities were inadequate and the situation was worst for primary educational institutions. Three institutions were found having a distance of less than 10m between toilet and source of drinking water which indicated the risk of ground water pollution.